2018
DOI: 10.1177/2158244018768657
|View full text |Cite
|
Sign up to set email alerts
|

Migration, Metaphor and Myth in Media Representations: The Ideological Dichotomy of “Them” and “Us”

Abstract: By focussing on the dichotomized metaphorical strategy and myth creation, this study aims to analyze how the U.S. and the European Union (EU) media respond to the entrenched metaphor of migration and refugee "crisis". In this respect, the U.S. and the EU media sources covering the time period from 2015 to 2016 were collected and analyzed in the theoretical framework of conceptual metaphor theory and critical metaphor analysis. By applying the metaphor identification procedure, it has been determined that most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 42 publications
0
38
0
1
Order By: Relevance
“…Therefore, although there has been 'a shift from a humanitarian discourse of pity to a post humanitarian discourse of irony' (Chouliaraki, 2012, 13), both paradigms cannot resolve the ambivalence of refugee representations on the media, or even aknowledge the agency of refugees as individuals with their own will, wishes and personalities. This insolvability perpetuates and reinforces the media representations of refugees either as voiceless objects of humanitarian intervention or as dangerous threats as well as the ideological dichotomy of 'us' versus 'them' (Arcimaviciene and Baglama, 2018): in any case, this has an influence on the formation, redefinition and representation of refugees and their cultural identity.…”
Section: The 'Refugee' Across Disciplinesmentioning
confidence: 96%
“…Therefore, although there has been 'a shift from a humanitarian discourse of pity to a post humanitarian discourse of irony' (Chouliaraki, 2012, 13), both paradigms cannot resolve the ambivalence of refugee representations on the media, or even aknowledge the agency of refugees as individuals with their own will, wishes and personalities. This insolvability perpetuates and reinforces the media representations of refugees either as voiceless objects of humanitarian intervention or as dangerous threats as well as the ideological dichotomy of 'us' versus 'them' (Arcimaviciene and Baglama, 2018): in any case, this has an influence on the formation, redefinition and representation of refugees and their cultural identity.…”
Section: The 'Refugee' Across Disciplinesmentioning
confidence: 96%
“…News media appear to differ in coverage when RAS are differently conceptualized, depending on geographical, political, or historical considerations [14], [31], [33]. A significant relationship has been found between media representations and public attitudes about RAS [23], [34], [35].…”
Section: B Representation Of Refugees and Asylum Seekers In Mediamentioning
confidence: 99%
“…Media also play an agenda-setting role, for instance, in discussing migration in the context of welfare, economy, or security (Buchanan et al, 2003;Moses, 2006, p. 137-43;Eberl et al, 2018). Multiple studies, for instance, have demonstrated how American and European media have framed migrants in a negative way, either by emphasizing the dichotomy of "us" vs. "them" or by creating an urgency of crisis (Cottle, 2000;Cisneros, 2008;Arcimaviciene and Baglama, 2018;Eberl et al, 2018;Viola and Musolff, 2019). Similarly, with reference to the UK migration debate, it has been argued that "the media are active agents in developing immigration policy" (Threadgold, 2009).…”
Section: The Role Of Media In the Construction Of Migration Discoursementioning
confidence: 99%